Optical System Design of a Portable Non-Mydriatic Fundus Camera for Diabetic Retinopathy Screening - Intan Fitri Hardyanti; Andi Bintang Adi Putra; Ahmad Harisul Hikam; Andi Nur Nabila Syalwani; Ricardo Bryan Nitbani; Dhany Arifianto; Shoffi Izza Sabilla (Program Vokasi UNG, 2026)
Diabetic Retinopathy (DR) is a leading microvascular complication of Diabetes Mellitus and the primary cause of preventable blindness globally. Early detection requires portable and affordable fundus imaging systems. This article presents the optical system design of EyeXaminer, a portable non-mydriatic fundus camera built around a Volk 90D aspheric lens (P = 90 D, f = 11.11 mm) and an Arducam NoIR IMX219 camera sensor (pixel pitch 1.12 µm). The optical design achieves a 0.876× magnification with a 19 mm sensor-to-lens working distance, yielding a spatial resolution of 1.28 µm/pixel at the retinal plane—sufficient to resolve retinal vessels and microaneurysms. The system employs 850 nm near-infrared LED illumination to maintain pupil dilation without pharmacological agents. Testing demonstrates successful acquisition of clear fundus images with well-delineated retinal structures after CLAHE pre-processing.